Erratum: Estimating Free and Added Sugar Intakes in New Zealand; Nutrients 2017, 9, 1292 - Kibblewhite R; Nettleton A; McLean R; Haszard J; Fleming E; Kruimer D; Te Morenga L (MDPI (Basel, Switzerland), 2018)
The authors have requested that the following changes be made to their paper. In Figure 1, the caption was changed to “Figure 1. 10–step method for estimating free sugars content (adapted from Louie et al. 2015 [14])”. In Appendix A, “This appendix details how we used and adapted the 10-step methodology for estimating added sugars described by Louie et al. 2015 [14] to calculate free sugars in the New Zealand food composition database, based on analytical data on total sugars and ingredients in food products. We used the unmodified Louie method to estimate added sugars in the New Zealand food composition database as reported in this paper” [2] was inserted in front of the Appendix A title. Further, “adapted from Louie et al., 2015 [14]” [2] was added after the title. “as per Step 1 of Louie et al., 2015 [14]” [2] was added in Step 1. “as per Step 2 of Louie et al., 2015 [14]” [2] was added in Step 2. “adapted from Step 3 of Louie et al., 2015 [14]” [2] was added in Step 3. “as per Step 4 of Louie et al., 2015 [14]” [2] was added in Step 4a; “adapted from Step 4 of Louie et al.2015 [14]” [2] was added in Step 4b. “as per Step 5 of Louie et al., 2015 [14]” [2] was added in Step 5. “as per Step 6 of Louie et al., 2015 [14]” [2] was added in Step 6. “adapted from Step 7 of Louie et al., 2015 [14]” [2] was added in Step 7. “as per from Step 9 of Louie et al., 2015 [14]” [2] was added as the last sentence of Step 9. “adapted from Step 10 of Louie et al., 2015 [14]” [2] was added as the last sentence of Step 10.
Keywords: 0908 Food Sciences; 1111 Nutrition and Dietetics